Representasi Feminisme dalam Serial Drama Lokal Induk Gajah (Analisis Wacana Kritis Model Sara Mills) - Sthevani, Kezia; Azeharie, Suzy (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Amazon Prime Video is a streaming service that provides local and international movies. On March 23, 2023, Amazon Prime Video officially released a local drama series entitled